2015
DOI: 10.1038/tp.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in mania phenotype and ethanol consumption in the lateral hypothalamic kindled rat model

Abstract: Sex differences have been observed in mania phenotypes in humans. However the mechanisms underlying this difference are poorly understood. Activating the lateral hypothalamus is implicated in manic-like behaviors in rodents. Using newly established lateral hypothalamus kindled (LHK) rat mania model, we investigated sex differences of manic-like behaviors and its correlation with voluntary ethanol intake. We stimulated the lateral hypothalamus bilaterally in the male and female Wistar rats over five consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…In our preclinical LHK rat model of mania, male rats showed a nonsignificant trend (p = .0516) toward increased sexual behavior compared with female rats (Abulseoud et al, 2015). Further studies are needed to investigate the phenomenology and neurobiological basis of sex differences in impulsive behaviors during manic episode.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In our preclinical LHK rat model of mania, male rats showed a nonsignificant trend (p = .0516) toward increased sexual behavior compared with female rats (Abulseoud et al, 2015). Further studies are needed to investigate the phenomenology and neurobiological basis of sex differences in impulsive behaviors during manic episode.…”
Section: Discussionmentioning
confidence: 84%
“…In agreement with our findings, one cross‐sectional study reported that male manic patients scored significantly higher on the sexual interest item than female patients upon admission to inpatient unit (Young et al, ). In our preclinical LHK rat model of mania, male rats showed a nonsignificant trend ( p = .0516) toward increased sexual behavior compared with female rats (Abulseoud et al, ). Further studies are needed to investigate the phenomenology and neurobiological basis of sex differences in impulsive behaviors during manic episode.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Also, acute amphetamine treatment cannot represent the chronic symptoms of schizophrenia and bipolar disorder. Thus, it will be important to examine the effects of PD149163 in other rodent models of mania- and schizophrenia-like behaviors [65, 66]. …”
Section: Discussionmentioning
confidence: 99%